(3GdeUHGMs - (3fGUQ Hf YHO GdSjO CHj GdecGQe GHf Ydj, CHh GdaJM, HQgGf GdOjf GdNhGQRej GdeWQRj , J (B610 (3g`s ((3CMeO Hf YKeGf s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Pi GdCfYGe , LGYd GdfMh ai GdcdGe cGdedM ai GdWYGe hGdUdGI Ydi fHjg eMeO SO GdCfGe hYdi Bdg hCUMGHg eDjOi GdESdGe s
(3BNQgG (B:s
(3hGdEVeGQ HOhf Pdc dGjLhR hbQjH ef gPG GdEVeGQ Ydi TQjWI GdJaSjQ dCf GdOGd Ydjg GdaX CjVkG EdG Cfg jYbHg hai GdChd eG SHb efg GdcdGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B71 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B488s
Keywords: (3GdfMhs